2014
DOI: 10.1155/2014/840923
|View full text |Cite
|
Sign up to set email alerts
|

Guided Imagery for Stress and Symptom Management in Pregnant African American Women

Abstract: The purpose of this study was to evaluate the efficacy of a guided imagery (GI) intervention for stress reduction in pregnant African American women beginning early in the second trimester. This prospective longitudinal study of 72 women used a randomized controlled experimental design with two groups conducted over 12 weeks. The intervention was a CD with 4 professionally recorded tracts designed and sequenced to influence study variables. Participants in both GI and usual care (UC) completed measures and don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 62 publications
(105 reference statements)
2
37
0
10
Order By: Relevance
“… relaxation (Bastani et al., ; Chang et al., ; Teixeira et al., ; Tragea, Chrousos, Alexopoulos, & Darviri, ; Ventura, Gomes, & Carreira, ) guided imagery (Jallo, Ruiz, Elswick, & French, ; Korol & Von Baeyer, ; Urech et al., ) mindfulness (Guardino et al., ; Vieten & Astin, ; Woolhouse et al., ) yoga (Davis et al., ; Newham et al., ; Satyapriya et al., ). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… relaxation (Bastani et al., ; Chang et al., ; Teixeira et al., ; Tragea, Chrousos, Alexopoulos, & Darviri, ; Ventura, Gomes, & Carreira, ) guided imagery (Jallo, Ruiz, Elswick, & French, ; Korol & Von Baeyer, ; Urech et al., ) mindfulness (Guardino et al., ; Vieten & Astin, ; Woolhouse et al., ) yoga (Davis et al., ; Newham et al., ; Satyapriya et al., ). …”
Section: Resultsmentioning
confidence: 99%
“…Some authors described the theoretical basis for CBT interventions (Bittner et al., ; Milgrom et al., ), psychological support/CBA interventions (Brugha et al., ; Côté‐Arsenault et al., ) and mind‐body interventions such as acupressure (Bastani, ), mindfulness (Guardino et al., ; Vieten & Astin, ; Woolhouse et al., ), guided imagery (Jallo et al., ), yoga (Newham et al., ; Satyapriya et al., ) and relaxation (Bastani et al., , Chang et al., ; Teixeira et al., ; Tragea et al., ; Urech et al., ; Ventura et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information on the design and methods of four of the studies can be found in the original reports (Ameringer et al, 2014; Jallo, Ruiz, Elswick, & French, 2014; Menzies et al, 2014; Robins et al, 2015). One study examined fatigue in fibromyalgia (FMS) (Menzies et al, 2014), another in sickle cell disease (SCD) (Ameringer et al, 2014), a third in cardiometabolic risk (CMR) (Robins et al, 2015), and a fourth in pregnancy (Jallo et al, 2014). In the fifth study, fatigue was examined in healthy controls and women with breast cancer; here, data from the healthy control subsample were used to examine known groups validity only.…”
Section: Methodsmentioning
confidence: 99%